Genetic variability and geographic distribution of peanut Arachis hypogaea L. in Ucayali, Peru - Rimachi, Luis Fernando (2012)
Peru has been recognized as one of the most important centers of diversity of the peanut crop and according to archaeological evidence, may have been the center of origin for it. Due to poor knowledge of the current levels of genetic diversity of peanut in Peru, they were evaluated 65 peanut accessions, corresponding to 21 local varieties from the basins of the rivers San Alejandro, Ucayali and Aguaytia, in the Ucayali region; kindly provided by the project "Models of diversity and genetic erosion of traditional crops: Rapid advice and early detection of risks using GIS tools", performed at the “Instituto Nacional de Innovacion Agraria”. AFLP technique was used to estimate the genetic variability of the crop in the region and to identify areas with the greatest genetic wealth. There were a total of 157 polymorphic bands (45.6%), from 10 AFLP primer combinations in our 65 entries of peanuts. We considered only 135 polymorphic bands, based on their polymorphic information content (0.1